2019
DOI: 10.1016/j.jcmg.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Entropy Is a Novel Predictor of Arrhythmic Events in Patients With Dilated Cardiomyopathy Receiving Defibrillators for Primary Prevention

Abstract: Automated LV entropy measurement is a novel marker for risk stratification toward ventricular arrhythmia in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…These results are in agreement with [20], as Muthalaly et al concluded that high LV entropy is a predictor of forthcoming arrhythmias.…”
Section: The Effect Of Scar's Micro-structure On the Defibrillation Ssupporting
confidence: 89%
“…These results are in agreement with [20], as Muthalaly et al concluded that high LV entropy is a predictor of forthcoming arrhythmias.…”
Section: The Effect Of Scar's Micro-structure On the Defibrillation Ssupporting
confidence: 89%
“…Moreover, CMR-TA has potential use in identifying which patients remain at high risk of VA, which is of growing interest in prophylactic VT ablation in the ICM cohort, where it could play a role in patient selection. Its use in the NICM population is less clear given our findings significantly differ from the Harvard-Leiden groups, 18 albeit with different scar inclusion methods and therefore method refinement and further larger multi-centre studies are warranted.…”
Section: Predictors Of Appropriate Icd Therapy and Clinical Translationmentioning
confidence: 72%
“…All subjects were scanned on the same 1.5T scanner, therefore we do not know how filtered mean entropy values vary with 3T or indeed different manufacturers. Muthalaly et al (2018), noted a difference in unfiltered entropy values between 1.5T and 3T in their NICM cohort and therefore further assessment is required in future studies. 18 Furthermore, we do not know whether there is temporal variation in entropy values and also recognise that inversion times, timing of LGE acquisition and additional imaging factors are unknown and required assessment.…”
Section: Commented [20]mentioning
confidence: 94%
See 2 more Smart Citations